1996
DOI: 10.1111/j.1440-1835.1996.tb00385.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of macroalgae in epiphytism of the toxic dinoflagellate Gambierdiscus toxicus (Dinophyceae)

Abstract: Populations of the toxic, epiphytic dinoflagellate Gambierdiscus toxicus Adachi et Fukuyo are associated closely with Jania sp. on Hitiaa and Papara fringing reefs in Tahiti. Small populations were also observed to be associated with Amphiroa sp. and Halimeda opuntia (L.) Lamouroux. The cells attached themselves to the thallus by means of a short thread. When the thalli were irradiated, the cells began to detach from them and swim around the branches. The swimming cells stopped and attached to substrata when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 9 publications
0
39
0
3
Order By: Relevance
“…In contrast, on macrophytes bloom populations of G. toxicus were high at the fringing reefs in Tahiti, Yasumoto et al, (1979), Papara reef (Nakahara et al, 1996), and Hitiaa reef (Bagnis et al, 1990). Yasumoto et al, (1980);and Ballantine et al, (1988) illustrated that G. toxicus cells formed a mucilaginous matrix over the macroalgal surface.…”
Section: Epiphytic and Benthic Dinoflagellate Communitymentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, on macrophytes bloom populations of G. toxicus were high at the fringing reefs in Tahiti, Yasumoto et al, (1979), Papara reef (Nakahara et al, 1996), and Hitiaa reef (Bagnis et al, 1990). Yasumoto et al, (1980);and Ballantine et al, (1988) illustrated that G. toxicus cells formed a mucilaginous matrix over the macroalgal surface.…”
Section: Epiphytic and Benthic Dinoflagellate Communitymentioning
confidence: 99%
“…Yasumoto et al, (1980);and Ballantine et al, (1988) illustrated that G. toxicus cells formed a mucilaginous matrix over the macroalgal surface. Nakahara et al, (1996) observed G. toxicus cells attached or cells swimming around on the thallus of Janina sp. ; and Coolia canariensis species attached to epiphytes on rocks at the tidal pools in the Canary Islands (Fraga et al, 2008).…”
Section: Epiphytic and Benthic Dinoflagellate Communitymentioning
confidence: 99%
See 2 more Smart Citations
“…Una de las posibles causas que pudieron afectar son las características de los sitios, ya que estos están compuestos principalmente por rompeolas, los cuales cumplen la función de disminuir la fuerza de llegada del oleaje a la costa. No obstante, estos ocasionan que incremente la turbulencia dado el choque de estas corrientes hacia las rocas, de tal forma que es posible que la adhesión efectiva de los dinoflagelados epífitos sobre las macrófitas disminuya, haciendo que se suspendan en la columna de agua (NAKAHARA et al, 1996;RICHLEN y LOBEL, 2011). Además, se observó una fuerte deposición de sedimento sobre la mayoría de macrófitas, que también afecta la colonización de estos microorganismos (DELGADO et al, 2006).…”
Section: Discussionunclassified